Derivational Morphemes on Webtoon “Smile Brush” by Waroo: A Morphology Analysis - Martini, Martini; Taufiq, M. Aries; Wulansari, Dini; Indriyani, Vivi; Asmawati, Asmawati (Universitas Cokroaminoto Palopo, 2025)
This study aimed to identify and analyze derivational morphemes found in the Smile Brush Webtoon by Waroo, focusing on their types, word-formation processes, and their effects on word class and meaning. Derivational morphemes played an essential role in vocabulary expansion by changing grammatical categories and enriching lexical meaning. This research employed a qualitative descriptive method, using the morphological theory of Haspelmath and Sims (2010) to classify the data and focused on the role of affixation in word formation within digital media contexts. The data were collected from episodes 1 to 35 of the Webtoon, resulting in a total of 20 derivational morphemes, consisting of 16 suffixes and 4 prefixes. These morphemes were categorized into ten derivational processes, including verb to noun (dis-, -ment), adjective to noun (-ness), noun to noun (auto-, -ian), verb to verb (re-), noun to verb (un-), verb to adjective (-ful), noun to adjective (-less, -ous, -ful), and adjective to adverb (-ly). The most frequent derivation type was adjective to adverb, marked by the use of the suffix -ly, with a total of eight occurrences. The findings indicated that derivational morphemes significantly contributed to the transformation of grammatical categories and the expansion of word meanings. The dominance of suffix usage over prefixes suggested that suffixes were more productive in the morphological structure of digital narrative texts. This research provided insight into the use of derivational morphology in contemporary media and served as a reference for future linguistic analysis in digital content.